Simultaneous mitigation of cadmium and drought stress in wheat by soil application of iron nanoparticles. (January 2020) - Adrees, Muhammad; Khan, Zahra Saeed; Ali, Shafaqat; Hafeez, Muhammad; Khalid, Sofia; ur Rehman, Muhammad Zia; Hussain, Afzal; Hussain, Khalid; Shahid Chatha, Shahzad Ali; Rizwan, Muhammad
Abstract: Excess amount of cadmium (Cd) in arable soils and shortage of good quality water are the major abiotic factors affecting the crop yield which needs immediate solution to feed the increasing population worldwide. Recently, nanoparticles (NPs) are widely used in various industries including agriculture which is due to the unique properties of NPs. Among NPs, iron (Fe) NPs might be used to alleviate the abiotic stresses in crops but limited informations are available in the literature about the role of Fe-NPs in crops under metal stress. The present study was designed to highlight the efficiency of Fe-NPs on Cd accumulation in Cd and drought-stressed wheat. Wheat plants were grown in Cd-contaminated soil after the supply of different levels of Fe-NPs and two water regimes were introduced in the soil in latter growth stages of the plants. Cadmium and drought stress negatively affected the wheat photosynthesis, yield and caused oxidative stress in leaves with excess accumulation of Cd in grains and other plant tissues. The NPs improved the photosynthesis, yield, Fe concentrations and diminished the Cd concentrations in tissues. The NPs alleviated the oxidative stress in leaves and the efficiency depends on the NPs concentrations applied in the soil. The results obtained indicated that Fe-NPs may be employed aiming to get wheat grains with excess Fe and decreased Cd contents. However, field investigations with various sizes, shapes and levels of NPs are needed before final recommendations to the farmers. Highlights: Combined cadmium (Cd) and drought decreased the yield of wheat. Drought stress increased the Cd concentration in grains of wheat. Iron oxide nanoparticles (Fe NPs) increased the wheat growth under Cd + drought stress. Fe NPs increased photosynthesis and reduced oxidative stress in Cd and drought-stressed wheat. Fe NPs decreased Cd and increased Fe concentrations in wheat grains.